2015
DOI: 10.1590/1678-775720140291
|View full text |Cite
|
Sign up to set email alerts
|

Novel biological activity of ameloblastin in enamel matrix derivative

Abstract: Objective Enamel matrix derivative (EMD) is used clinically to promote periodontal tissue regeneration. However, the effects of EMD on gingival epithelial cells during regeneration of periodontal tissues are unclear. In this in vitro study, we purified ameloblastin from EMD and investigated its biological effects on epithelial cells.Material and Methods Bioactive fractions were purified from EMD by reversed-phase high-performance liquid chromatography using hydrophobic support with a C18 column. The mouse ging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The effects of AMBN in adipocytes seem analogous to effects previously reported in non-mineralizing ameloblasts, e.g. both cell types express a short AMBN splice variant, a translated AMBN C-terminus variant (Lee et al., 2003; Ravindranath et al., 2007), and administration of rAMBN reduce proliferation (Fukumoto et al., 2004; Fukumoto et al., 2005; Kuramitsu-Fujimoto et al., 2015; Sonoda et al., 2009; Y. B. Zhang et al., 2011).…”
Section: Discussionsupporting
confidence: 70%
“…The effects of AMBN in adipocytes seem analogous to effects previously reported in non-mineralizing ameloblasts, e.g. both cell types express a short AMBN splice variant, a translated AMBN C-terminus variant (Lee et al., 2003; Ravindranath et al., 2007), and administration of rAMBN reduce proliferation (Fukumoto et al., 2004; Fukumoto et al., 2005; Kuramitsu-Fujimoto et al., 2015; Sonoda et al., 2009; Y. B. Zhang et al., 2011).…”
Section: Discussionsupporting
confidence: 70%
“…In addition, a previous study demonstrated that recombinant AMEL inhibits epithelial cell proliferation in vitro . The results of Kuramitsu-Fujimoto et al (35) suggest that ameloblastin is the primary bioactive factor of EMD in regards to inhibition of epithelial cell proliferation. It has been suggested that EMPs, such as AMELs and ameloblastin, are required for enamel biomineralization and have synergistic cellular functions (36).…”
Section: Discussionmentioning
confidence: 99%
“…As the process unfolds, weeks after EMD application, bioactive peptides are released around the periodontal defect [10]. EMD contains as well enamelin and ameloblastin [13], the last one being involved in the inhibition of epithelial cell proliferation [14]. Furthermore, the vehicle solution, PGA, has proved to have antimicrobial properties on the bacteria associated with periodontal disease [15].…”
Section: Introductionmentioning
confidence: 99%